2008
DOI: 10.5005/jp-journals-10005-1001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoride Varnish on Streptococcus mutans Count in Saliva of Caries Free Children Using Dentocult SM Strip Mutans Test: A Randomized Controlled Triple Blind Study

Abstract: Aims: The aim of this study was to estimate the count of Streptococcus mutans in saliva of caries free children using Dentocult SM strip mutans and to evaluate the effect of fluoride varnish on the Streptococcus mutans count in saliva of these caries free children.Methods and material: Thirty caries free children were selected for the study based on the information obtained from a questionnaire prepared. They were randomly assigned into the control group and the study group consisting of ten and twenty childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…S. mutans has been introduced as the main species of caries-causing bacteria due to its strong acid production and high tolerance to acidic conditions ( Sales-Campos et al., 2019 ; Hasslöf and Stecksén-Blicks, 2020 ). Research has shown that the number of S. mutans in the saliva of people without caries is normally between 10 4 and 10 5 CFU/mL ( Deepti et al., 2008 ), But at 10 6 CFU/mL, the risk of caries increases significantly ( Klock and Krasse, 1979 ). In this regard, 10 5 CFU/mL has been considered the threshold of caries in clinical studies ( Caglar et al., 2008b ; Ghasemi et al., 2017 ; Bafna et al., 2018 ).…”
Section: Lactobacillus Bacteria and Oral Healthmentioning
confidence: 99%
“…S. mutans has been introduced as the main species of caries-causing bacteria due to its strong acid production and high tolerance to acidic conditions ( Sales-Campos et al., 2019 ; Hasslöf and Stecksén-Blicks, 2020 ). Research has shown that the number of S. mutans in the saliva of people without caries is normally between 10 4 and 10 5 CFU/mL ( Deepti et al., 2008 ), But at 10 6 CFU/mL, the risk of caries increases significantly ( Klock and Krasse, 1979 ). In this regard, 10 5 CFU/mL has been considered the threshold of caries in clinical studies ( Caglar et al., 2008b ; Ghasemi et al., 2017 ; Bafna et al., 2018 ).…”
Section: Lactobacillus Bacteria and Oral Healthmentioning
confidence: 99%
“…S. mutans count in saliva was statistically significantly lower after using fluor protector fluoride varnish, according to Deepti et al . [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Co. Ltd., Japan) at baseline and at 6-month follow-up. Dentocult ® SM determined the colony forming units (CFU) of mutans streptococci in dental plaque and saliva [14,15]. Cariostat ® detected the degree of acid production by cariogenic bacteria in the dental plaque [16].…”
Section: Caries Risk Testsmentioning
confidence: 99%